Fertilizer policy in Bangladesh: State intervention in markets and prices - Islam, Nurul; Mujeri, Mustafa K. (University Press Limited, 2021)
Bangladesh has achieved commendable progress in agriculture especially in increasing food grains production over the past few decades. Three mutually supportive mechanisms have operated in different degrees for expanding agricultural (food) production in Bangladesh during the period: first, the increase in efficiency of use of farm inputs and technologies; second, using more productive inputs; and third, adopting improved technologies. Among the three, the first two have helped the small and marginal farmers (who form the overwhelming majority in Bangladesh agriculture) to experience the immediate benefits of higher farm outputs, contributing to an increased income and better living conditions. The third has been particularly important in enhancing the welfare of the consumers (resulting from lower real food prices) including the largest segment of the poor households in both rural and urban areas who are net buyers of food in Bangladesh (Mujeri, Shahana, Chowdhury, and Haider 2013).